Developing Creative Thinking and Composition Skills through Visual Arts in Secondary School Students - G‘aybullayeva Mehribon G‘olibovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the pedagogical foundations for developing creative thinking and composition skills in secondary school students through visual arts. Visual arts enhance students’ artistic thinking, aesthetic taste, and the ability to make creative decisions. The study analyzes effective methods and approaches based on the research of Shovdirov S. A. and other scholars. Additionally, the article highlights the role of interactive teaching methods and modern technologies in fostering students’ creative abilities and compositional understanding.